An induction of basic structure doctrine in Malaysian jurisprudence and Federal Constitution: an overview - Muhammad Hassan,; Johan Shamsuddin Sabaruddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research work explores the historical formation of the Federal Constitution. Further, the object of this study is to elaborate the scope of the sovereignty of the Malaysian parliament and its implied embedded limitation with regard to amending the salient features of the Federal Constitution. The author also discusses the historical background of inception and rejection of the Basic Structure Doctrine in the Malaysian jurisprudence. In pursuance of inception and rejection, three leading cases are also critically discussed. Moreover, the authors also discuss three leading cases wherein the Federal Court formally adopted basic structure doctrine and overlooked its own previous rejection approach. Lastly, it concludes that the scheme of the Federal Constitution indicates that there are various implied substantive limitations over the amending power of the parliament even in the absence of preamble and directive principles.